On Some Identites and Generating Functions for (s,t)-Pell and (s,t)-Pell-Lucas Numbers - Srisawat, Somnuk; Sriprad, Wanna (Progress in Applied Science and Technology, 2017)
In this paper, we obtain the Binet’s formula for (s,t)-Pell and (s,t)-Pell-Lucas numbers and then we get some identities for these numbers by using the Binet’s formula. Moreover, we obtain the generating functions for (s,t)-Pell and (s,t)-Pell-Lucas sequences and another expression for the general term of the sequences by using the ordinary generating functions.